Angivelse av verbkonstruktioner i svenska ordböcker - Martola, Nina (Nordiske Studier i Leksikografi, 2007)
In this study I analyze how verb valency is treated in five Swedish monolingual dictionaries with the preposition åt (‘to; for; at’) as example. I also look at the presentation of phrasal verbs with åt. Initially I examine how prepositional particles are classified as lemmas, and I can establish that in most dictionaries they are looked upon as adverbs. As to the valency information the differences between the dictionaries are considerable, but in general one can say that the larger dictionaries, not unexpectedly, cover verb valencies better than the shorter ones. The larger dictionaries also give more explicit information while the shorter dictionaries give valency information only in the form of (causal) examples. The most problematic items are the phrasal verbs. In two of the analyzed dictionaries the treatment is good, though. The phrasal verbs are given as sublemmas after the verb entry with their own descriptions. The other three dictionaries subsume phrasal verbs in the verb article, and it is not always clear whether åt is a valency preposition or a particle in the given examples. One of the dictionaries even mix prepositions and particles in the formal constructional information.